TALK: Topology Aware LKH Key Management. (18th November 2014) - Tsitsipis, Dimitris; Tzes, Anthony; Koubias, Stavros
Cryptographic key management for wireless sensor networks (WSNs) and mobile ad-hoc networks (MANETs) is a particularly challenging task, as they mostly consist of high counts of resource constrained nodes, especially when group communication and dynamic network membership capabilities are required. The logical key hierarchy (LKH) is a well-known class of protocols which aims to solve the key management problem and minimize rekeying overhead, using hierarchical structures and taking advantage of multicast communication. In this work we propose a method for obtaining LKH structures by taking into account the topology of the underlying network, leading to a further decrease in rekeying costs, in terms of packet transmissions.